COMPARISON OF EFFECTIVENESS BETWEEN AMARANTHUS SPINOSUS L. LEAF EXTRACT AND SAUROPUS ANDROGYNUS (L.) MERR. TOWARDS BREAST MILK PRODUCTION ON FEMALEÂ WISTARÂ RATS - Mithwa Anisa, Alfina
Breast milk is an important nutrient for newborn babies. Breast milk contains a number of important components that are beneficial for the growth of babies. Many mothers face problems and challenges in breastfeeding their children, such as insufficient amounts of milk supply (lactation insufficiency). The production of milk is influenced by food consumption. Consumption of katuk leaves (Sauropus androgynus (L.) Merr.) or spiny amaranth leaves (Amaranthus spinosus L.) are believed to be able to increase milk production. This study was aimed to compare the effectiveness between katuk leaves and spiny amaranth or spinach leaves in increasing milk production. In order to conduct the study, female postpartum Wistar rats were given ethanol extracts of katuk and spinach leaves for 14 days of treatment. Positive control was given metoclopramide, while negative control was given CMC-Na 0.5%. The estimated amount of milk production is based on the increase in the body weight of the rats after the lactation period. To determine the milk yield of each rat, the rat’s weight gain is processed and corrected. The results of the control group and the test group were compared statistically with the one-way ANOVA method. After 14 days of treatment, the whole group generally experienced a continuous increase of milk yield. The highest milk yield was shown in the spinach leaf extract group at a dosage of 180 mg/kg BB (15.11 ± 2.084 mg/kg/day). Significant differences (P < 0.05) were shown in the 180 mg/kg BB spinach leaf extract group with a result 134% higher than the negative control. The highest daily intake rate of 7.675 ± 3.194 g/day was achieved by the spinach leaves group 180 mg/kg. Based on the results of this study, it can be concluded that spinach leaf extract at a dose of 180 mg/kg BB is more effective (P<0.05) than the negative control group in increasing milk production of postpartum female Wistar rats after administering the extracts for 14 days.